Cloning, bioinformatics and transcriptional analysis of caffeoyl-coenzyme A 3-O-methyltransferase in switchgrass under abiotic stress - Si-jia LIU; Yan-hua HUANG; Chang-jiu HE; Cheng FANG; Yun-wei ZHANG (Journal of Integrative Agriculture, 2016)
Genes encoding enzymes involved in the lignin biosynthesis through phenylpropanoid pathway were not only associated with the lignin content, but also related to the abiotic stress resistances. As far as the production of liquid biofuels and cultivation within the marginal land are concerned, switchgrass could be the better candidate to determine the relationship between lower lignin content and physiological function under stress. Caffeoyl-coenzyme A 3-O-methyltransferase (CCoAOMT) is a key enzyme for the methylation reaction of lignin biosynthesis. For this purpose, we cloned a CCoAOMT gene from switchgrass and identified its expression patterns under abiotic stresses. The full-length CCoAOMT gene, designated PvCCoAOMT (GenBank accession no. KF041775), was 1005-bp in length, has an opening reading frame of 777 nucleotides encoding a 258-amino acid protein. The deduced amino acid sequence of PvCCoAOMT shared a high degree of similarity (up to 98%) with CCoAOMTs from Panicum virgatum allele (BAO20881), Sorghum bicolor (XP002436550) and Zea mays (NP001131288). Using quantitative real-time PCR (qRT-PCR), the significant upregulation of PvCCoAOMT was observed in stem tissues at a later stage (24 h) after drought treatment, with the transcript level increasing 33-fold compared that of the controls. Moderate and insignificant inductions of PvCCoAOMT were also observed in both stems and leaves during the later stages after cold (48 h in stems, 12 h in leaves) and mechanical wounding (48 h in stems, 12 h in leaves) treatments, respectively. Our results showed the different expression patterns of PvCCoAOMT in drought, cold and mechanical wounding stresses. PvCCoAOMT can be highly induced by drought and cold stresses, which indicates that it may play a role in plant abiotic stress resistance, particularly in the regulation of drought and cold resistance.